2007
DOI: 10.1128/jb.00813-07
|View full text |Cite
|
Sign up to set email alerts
|

SpxB Is a Suicide Gene ofStreptococcus pneumoniaeand Confers a Selective Advantage in an In Vivo Competitive Colonization Model

Abstract: The human bacterial pathogen Streptococcus pneumoniae dies spontaneously upon reaching stationary phase. The extent of S. pneumoniae death at stationary phase is unusual in bacteria and has been conventionally attributed to autolysis by the LytA amidase. In this study, we show that spontaneous pneumococcal death is due to hydrogen peroxide (H 2 O 2 ), not LytA, and that the gene responsible for H 2 O 2 production (spxB) also confers a survival advantage in colonization. Survival of S. pneumoniae in stationary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
107
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 44 publications
6
107
1
1
Order By: Relevance
“…Given these examples of pathogens that have evolved mechanisms to induce DNA damage in mammalian cells, it seemed plausible that the host genome might be an intended target of S. pneumoniae. Indeed, in the case of S. pneumoniae, although it was known that the spxB gene worsens infection (51,52), our work points specifically to the ability of the spxB gene to induce DNA damage as the underlying driver of spxB-associated virulence. Furthermore, to date, the link between pathogen-induced DNA damage and disease has been focused primarily on cancer, whereas here we show an example of a pathogen-secreted DNA-damaging factor that has a direct association with pathogen-induced morbidity and mortality during infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these examples of pathogens that have evolved mechanisms to induce DNA damage in mammalian cells, it seemed plausible that the host genome might be an intended target of S. pneumoniae. Indeed, in the case of S. pneumoniae, although it was known that the spxB gene worsens infection (51,52), our work points specifically to the ability of the spxB gene to induce DNA damage as the underlying driver of spxB-associated virulence. Furthermore, to date, the link between pathogen-induced DNA damage and disease has been focused primarily on cancer, whereas here we show an example of a pathogen-secreted DNA-damaging factor that has a direct association with pathogen-induced morbidity and mortality during infection.…”
Section: Discussionmentioning
confidence: 99%
“…of having spxB in a nasopharyngeal colonization model (52). It has been reported that spxB inactivation in acapsular pneumococcal serotype 2 strain reduces its adherence to alveolar epithelial cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Centers for Disease Control (CDC), ϳ5 million fatal cases of pneumococcal pneumonia in children under the age of five are reported globally each year (37). Pneumococci have an unusual lifestyle because they produce high levels of hydrogen peroxide that provides a competitive advantage for the organism during colonization of the nasopharynx (1,2). In other organisms, it has been reported that exposure to increased levels of hydrogen peroxide can enhance cellular mistranslation rates both in vivo and in vitro (3,4).…”
mentioning
confidence: 99%
“…Following this process, the aminoacyl-tRNA is released from the synthetase and bound by elongation factor Tu (EF-Tu) 2 for delivery to the ribosome and use in protein synthesis (6,7). Aminoacyl-tRNA synthetases are usually highly selective for their cognate tRNA due to the availability of a large surface area for recognition, identity elements within the tRNA molecule itself, and also kinetic proofreading during the aminoacylation reaction (8 -10).…”
mentioning
confidence: 99%
“…LytA, an N -acetylmuramyl-l-alanine amidase, is important for peptidoglycan remodeling during growth [36] and appears to be constitutively expressed [37,38]. Death or suicide of S. pneumoniae in the stationary phase has been attributed to autolysis by LytA [38,39], however, it has been proposed that spontaneous pneumococcal death is due to hydrogen peroxide (H 2 O 2 ), a by-product of aerobic metabolism by SpxB, not LytA [40]. Taken together, not only cell wall attached proteins but also exposed Ccs4 may interact with host cells when host-pneumococcal contact induces LytA expression, causing degradation of the cell wall peptidoglycan and capsule.…”
Section: Discussionmentioning
confidence: 99%